Życie ludzkie na tle przestrzeni czasowej. Powieści M.A. Osorgina „Świadek historii” i „Książka o końcach” - Murawski, Antoni (Studia Rossica Posnaniensia, 2011)
The main theme of this article is specific perceiving of reality and the historical process in the novels of Mikhail Osorgin. The writer tries to explain the sense of socialistic movement in Russia and it’s consequence – the revolution and the civil war 1917–1919. According to the point of view of Osorgin, the catastrophe, which happened to his country, is a part of the natural evolution of the universe. For the author, human life is more important than political ideas. Osorgin explains that people should build their own happiness instead of sacrifying their lives for abstract goals, which means nothing in the face of the universe and infinity. These ideas are connected with cosmological ideology of Osorgin.